Expanding the scope: multimodal dimensions in aphasia discourse analysis—preliminary findings - Dutta, Manaswita; Mohapatra, Bijoyaa (Frontiers in Human Neuroscience, 2024)
Background: Aphasia, resulting from acquired brain injury, disrupts language processing and usage, significantly impacting individuals' social communication and life participation. Given the limitations of traditional assessments in capturing the nuanced challenges faced by individuals with aphasia, this study seeks to explore the potential benefits of integrating multimodal communication elements into discourse analysis to better capture narrative proficiency in this population.Objective: This study examined how incorporating multimodal communication elements (e.g., physical gestures, writing, drawing) into discourse analysis may affect the narrative outcomes of persons with aphasia compared to those observed using methods that exclude multimodal considerations.Methods: Participants included individuals with chronic aphasia and age-and education-matched healthy controls who completed a storytelling task -the Bear and the Fly story. Macrolinguistic scores were obtained using verbal-only and multimodal scoring approaches. Additionally, the frequency and type of multimodal communication use during storytelling were examined in relation to aphasia characteristics. Statistical analyses included both within-group and betweengroup comparisons as well as correlational analyses.Results: Individuals with aphasia scored significantly higher in terms of their macrolinguistic abilities when multimodal scoring was considered compared to verbal-only scoring. Within the aphasia group, there were prominent differences noted in macrolinguistic scores for both fluent and nonfluent aphasia. Specifically, both groups scored higher on Main Concepts when multimodal scoring was considered, with the nonfluent group demonstrating significantly higher Main Concept and total macrolinguistic rubric scores in multimodal scoring compared to verbal scoring on the storytelling task. Additionally, aphasia severity showed moderate positive correlations with total macrolinguistic scores, indicating that individuals with less severe aphasia tended to produce higher quality narratives. Lastly, although persons with aphasia used different types of nonverbal modalities (i.e., drawing, writing), the use of meaning-laden gestures was most predominant during storytelling, emphasizing the importance of multimodal elements in communication for individuals with aphasia.Our preliminary study findings underscore the importance of considering multimodal communication in assessing discourse performance among individuals with aphasia.Tailoring assessment approaches based on aphasia subtypes can provide valuable insights into linguistic abilities and inform targeted intervention strategies for improving communication outcomes.